Adaptation to nocturnality – learning from avian genomes. (12th May 2016) - Le Duc, Diana; Schöneberg, Torsten
Abstract : The recent availability of multiple avian genomes has laid the foundation for a huge variety of comparative genomics analyses including scans for changes and signatures of selection that arose from adaptions to new ecological niches. Nocturnal adaptation in birds, unlike in mammals, is comparatively recent, a fact that makes birds good candidates for identifying early genetic changes that support adaptation to dim‐light environments. In this review, we give examples of comparative genomics analyses that could shed light on mechanisms of adaptation to nocturnality. We present advantages and disadvantages of both "data‐driven" and "hypothesis‐driven" approaches that lead to the discovery of candidate genes and genetic changes promoting nocturnality. We anticipate that the accessibility of multiple genomes from the Genome 10K Project will allow a better understanding of evolutionary mechanisms and adaptation in general. Abstract : Comparative genomics is an exciting field that can pinpoint differences in genomic regions, which occur as a result of an environmental change. The future availability of multiple bird genomes opens an unprecedented era for research of mechanisms of nocturnal adaptation.